Space, Place and Children's Reading Development Mapping the Connections - Mackey, Margaret (Bloomsbury Perspectives on Children's Literature, 2022)
Based on a qualitative study into the experiences of readers when they were children, this is an innovative exploration of the effect of place and social geographies on reading development and textual interpretation.